Highly stereoselective synthesis of mupirocin H. Issue 8 (23rd February 2017) - Sengupta, Sandip; Kim, Hak Joong; Cho, Kyung Seon; Song, Woon Young; Sim, Taebo
Abstract: A highly diastereoselective and efficient convergent synthesis of mupirocin H starting from (+)-( R )-Roche ester was achieved. Grubbs cross metathesis was employed as the key step in the pathway to generate an important E -olefin intermediate. Other processes utilized in the route include a Pd-catalysed stereoselective substitution reaction of a cis epoxide, Sharpless epoxidation followed by Red-Al promoted epoxide ring opening, and Seebach methylation and a TEMPO/BAIB mediated oxidation-lactonization sequence. Finally, we observed that mupirocin H inhibits SbnE, a synthetase required for staphyloferrin B biosynthesis. Graphical abstract: